Evaluation of caries risk in a young adult population using a computer-based risk assessment model (Cariogram) - Ilkay Peker; Tandogan Mangal; Hulya Erten; Gulcin Alp; Emre Avci; Gulcin Akca (Elsevier, 2012)
Background/purpose: Cariogram is a software program which was recently developed for the practical application of caries-risk assessment. The purpose of this study was to evaluate the relationships between caries risk and different variables of Cariogram in a young adult population. Materials and methods: This study included 90 volunteers (49 females and 41 males) aged 19-25 years. Systemic diseases, diet frequency, fluoride programs, and the decayed, missing, and filled teeth (DMFT), decayed, missing, and filled surfaces (DMFS), and plaque indices were recorded by clinic and radiographic examinations. The saliva secretion rate, and Streptococcus mutans and Lactobacillus counts were determined by saliva sampling. Results: Statistically significant correlations were found between the caries risk determined by Cariogram and the past caries experience (DMFT and DMFS indices), fluoride programs, and S. mutans and Lactobacillus counts in the saliva. The results of a linear regression analysis showed that the most important factors for caries risk were the past caries experience, diet frequency, fluoride program, saliva secretion rate, and S. mutans and Lactobacillus counts. Conclusions: According to the results of this study, the most important factors for caries risk were the past caries experience, fluoride programs, and S. mutans and Lactobacillus counts in saliva. Cariogram is a helpful method for dentists in clinical practice to assess caries risk, and it can be used as a didactic tool for patient education and motivation.